The exercise of family power versus the autonomy of the intersexed minor in the light of personality rights (Revista Direito em Debate, 2022)
The intersexuality is a biological and physical condition identified by the birth of a person with characteristics (morphological, endocrinological and genetic) related to male and female, but, for the purposes of this research, only intersex cases characterized by genital ambiguity were considered. In Brazil there is no specific law that deal with the subject and for the traditional medical approach the indicated is that, once the intersexuality is verified, soon after the child is born, she must be undergo to medical examinations to determine its predominant sex and, subsequently, be submitted to a surgery to “correct” the genital. However, the procedure is invasive and represents an affront to a range of fundamental and personality rights, in particular the rights to identity and physical integrity. The present study aims to analyze the limits of family power and the possibility of recognination of the minor’s autonomy at the expense of the practice of surgical “correction” in the intersex newborns. The methodology used was the theoretical research, which consists in the consulting of websites, books, articles and laws related to the theme.